Astaxanthin Provides Antioxidant Protection in LPS-Induced Dendritic Cells for Inflammatory Control - Yinyan Yin; Nuo Xu; Tao Qin; Bangyue Zhou; Yi Shi; Xinyi Zhao; Bixia Ma; Zhengzhong Xu; Chunmei Li (Marine Drugs, 2021)
Astaxanthin, originating from marine organisms, is a natural bioactive compound with powerful antioxidant activity. Here, we evaluated the antioxidant ability of astaxanthin on dendritic cells (DCs), a key target of immune regulation, for inflammatory control in a sepsis model. Our results showed that astaxanthin suppressed nitric oxide (NO) production, reactive oxygen species (ROS) production, and lipid peroxidation activities in LPS-induced DCs and LPS-challenged mice. Moreover, the reduced glutathione (GSH) levels and the GSH/GSSG ratio were increased, suggesting that astaxanthin elevated the level of cellular reductive status. Meanwhile, the activities of antioxidant enzymes, including glutathione peroxidase (GPx), catalase (CAT), and superoxide dismutase (SOD), were significantly upregulated. Astaxanthin also inhibited the LPS-induced secretions of IL-1β, IL-17, and TGF-β cytokines. Finally, we found that the expressions of heme oxygenase 1 (HO-1) and nuclear factor erythroid 2-related factor 2 (Nrf2) were significantly upregulated by astaxanthin in LPS-induced DCs, suggesting that the HO-1/Nrf2 pathway plays a significant role in the suppression of oxidative stress. These results suggested that astaxanthin possesses strong antioxidant characteristics in DC-related inflammatory responses, which is expected to have potential as a method of sepsis treatment.